Highly chemoselective catalytic system for hydrogenation of diketones to ketols: an environmentally benevolent system - Deshmukh, Amit A.; Kinage, Anil K.; Kumar, Rajiv (Catalysis Letters, 2008)
Ru(Phen)(2)Cl-2 [Phen = Phenanthroline] anchored in organo-functionalized MCM-41 [Ru(Phen)(2)Cl-NH-MCM-41] efficiently catalyzes highly chemoselective hydrogenation of diketones to ketols (Sel. similar to 99%) under environmentally benign tri-phasic (solid-liquid-liquid) reaction condition in aqueous medium.
Keywords: Chemoselective; dione; Hydrogenation; ketol; ruthenium phenanthroline; Water

Highly selective synthesis of mono-ethylene glycol phenyl ethers via hydroxyalkoxylation of phenols by cyclic carbonates using large pore zeolites - Kinage, Anil K.; Gupte, Sunil P.; Chaturvedi, Rajiv K.; Chaudhari, Raghunath V. (Catalysis Communications, 2008)
Hydroxyalkoxylation of phenols by cyclic carbonates catalyzed by alkali loaded large pore zeolites has been reported. The study shows that KL type zeolite was recyclable and selective in producing mono-ethylene glycol pheryl ethers in similar to 98.5% yield. Various substituted simple phenols were converted into mono-ethylene glycol ether of phenols with over 90% yields, except 3-bromo and 2-methyl phenols. Mono hydroxyl plienols such as hydroquinone, biphenol and BPA (2,2-bis(4-hydroxyphenyl)propane) also produce corresponding mono- and di-ethylene glycol ethers. The ratio of ethylene carbonate to phenol was found to be critical for selective formation of monoethylene glycol phenyl ether of phenols. A ratio of two results in formation of appreciable amount of diether derivative viz., 2-(2-phenoxyethoxy) ethanol. Compared to ethylene carbonate, a lower reactivity of 1,2-propane carbonate was found for hydroxyalkoxylation of phenol. It was found that ring opening at less hindered methylene carbon of 1,2-propylene carbonate prevailed giving rise to selective formation of beta-hydroxy phenyl ethers. The reactivity of ethylene carbonate towards O-alkylation versus transesterification of phenol has been explained on the basis of HSAB concept. Finally, it has been shown that yield of mono-ethylene glycol phenyl ether is controlled both by basicity and channel architecture of zeolite structure. KL zeolite was found to be the most effective zeolite because of it's intermediate basicity and one dimensional channel architect. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: cyclic carbonate; ethylene glycol phenyl ether; hydroxyalkoxylation; phenol

Heterogenized Ru(II) phenanthroline complex for chemoselective hydrogenation of diketones under biphasic aqueous medium - Deshmukh, Amit A.; Kinage, Anil K.; Kumar, Rajiv; Meijboom, Reinout (Journal of Molecular Catalysis A-Chemical, 2010)
The chemoselective hydrogenation of acetylacetone to 4-hydroxypentan-2-one over immobilized ruthenium phenanthroline metal complexes in amino functionalized MCM-41 in biphasic aqueous reaction medium was investigated. The catalyst was characterized by XRD, TEM, surface analysis, FT-IR and UV-vis to understand the morphology, complex geometry, and XPS such that the oxidation state of the metal complex inside the MCM-41 framework could be understood. The use of water as a solvent, not only gives high activity and selectivity for hydrogenation of acetylacetone, but also gives a path for an environmentally safer process. The optimizations of ligand, metal to ligand ratio, the choice of solvent and other reaction parameters were studied in detail. The heterogeneous catalytic system gave a higher degree of chemoselectivity (99%) towards 4-hydroxypentan-2-one as compared to homogeneous catalyst when hydrogenation was carried out using water as a solvent. The immobilized ruthenium-phenanthroline complex was easily separated and reused. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: 4-Hydroxypentan-2-one; acetylacetone; Chemoselective; Diketone; Hydrogenation; Phenanthroline; ruthenium; Water